Government Social Media Communication as a Political Public Relations Strategy for Advancing Social Welfare - Muhammad Faisal; Andi Alimuddin Unde; Muhammad Farid; Mamoon Suliman Alsmadi; Mohamed W. Abouyounes (PT. Islamic Research Publiser, 2026)
This study examines how the regional head of East Kalimantan, following the 2024 regional election, leveraged social media as a political public relations strategy to enhance social welfare. It focuses on three key dimensions: communication mechanisms, the nature of disseminated content, and patterns of interaction between government and citizens in the digital sphere. Employing a descriptive qualitative design with a case study approach, the research draws on multiple data sources, including content analysis of official government social media accounts, in-depth interviews with key stakeholders, and participatory observation of public engagement. Data were analyzed thematically to identify recurring communication patterns, strategic orientations, and their implications for public perception and welfare outreach. The findings indicate that social media functions not merely as a tool for information dissemination but as a strategic platform for constructing an image of transparent, responsive, and participatory leadership. The regional head systematically used digital platforms to communicate about social welfare programs, foster dialogic engagement, and mobilize community participation through structured, consistent campaigns. Interactive and socially oriented communication practices were found to significantly strengthen public trust, expand policy visibility, and improve accessibility to welfare initiatives. Moreover, integrating feedback mechanisms enabled more adaptive, citizen-centered governance. This study contributes to the growing body of literature on digital political communication by offering empirical insights into the role of social media in local governance contexts. It advances understanding of political public relations as a dynamic, participatory process in the digital era. Practically, the findings guide policymakers and public officials in designing communication strategies that are not only effective but also socially impactful. The study also opens avenues for future research on the integration of digital platforms into public policy processes and innovative models of government communication management.